Response to letter from Tim Bailey - J.M. Wilkinson; R.H. Young (Journal of Applied Animal Nutrition)
Refers to: Tim Bailey Letter to the Editor on “Strategies to reduce reliance on soya bean meal and palm kernel meal in livestock nutrition” Journal of Applied Animal Nutrition: 8 (2)- Pages: 101 - 102